The Spare Room - Bartz, Andrea (Thorndike, Maine : Center Point Large Print, 2023)
"Kellys new life in Philadelphia has turned into a nightmare: Shes friendless and jobless, and the lockdown has her trapped in a tiny apartment with the man she gave up everything for, whos just called off their wedding. The only bright spot is her newly rekindled friendship with her childhood friend Sabrina -- now a glamorous bestselling author with a handsome, high-powered husband. When Sabrina and Nathan offer Kelly an escape hatch, volunteering the spare room of their remote Virginia mansion, she jumps at the chance to run away from her old life. There, Kelly secretly finds herself falling for both her enchanting hosts -- until one night, a wild and unexpected threesome leads the couple to open their marriage for her. At first, Kelly loves being part of this risqunew world. But when she discovers that the last woman they invited into their marriage is missing, she starts to wonder if they could be dangerous . . . and if she might be next."--
Keywords: Unemployed women workers -- Fiction; Non-monogamous relationships -- Fiction; Bisexual women -- Fiction; Open marriage -- Fiction; Secrecy -- Fiction; Friendship -- Fiction; COVID-19 Pandemic, 2020- -- Fiction; Virginia -- Fiction; Queer fiction; Psychological fiction; Erotic fiction; Thrillers (Fiction); Detective and mystery fiction; Large print books